2010
DOI: 10.1186/1757-4749-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni induces transcytosis of commensal bacteria across the intestinal epithelium through M-like cells

Abstract: BackgroundRecent epidemiological analyses have implicated acute Campylobacter enteritis as a factor that may incite or exacerbate inflammatory bowel disease (IBD) in susceptible individuals. We have demonstrated previously that C. jejuni disrupts the intestinal barrier function by rapidly inducing epithelial translocation of non-invasive commensal bacteria via a transcellular lipid raft-mediated mechanism ('transcytosis'). To further characterize this mechanism, the aim of this current study was to elucidate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…In line with previous studies (22,26,45), our data also provide support for a transcytosis-mediated model for C. jejuni translocation across host epithelia, including apical endocytosis and basolateral exocytosis.…”
Section: Discussionsupporting
confidence: 79%
“…In line with previous studies (22,26,45), our data also provide support for a transcytosis-mediated model for C. jejuni translocation across host epithelia, including apical endocytosis and basolateral exocytosis.…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of Campylobacter jejuni and other species, including C. concisus, is higher in patients with IBD than non-IBD controls; in one study of pediatric Crohn's disease [8], the prevalence by genus-specific PCR was 72% in fecal samples from children with Crohn's disease, significantly different than the 30% observed in healthy and non-IBD controls (Table 1). Although the significance of these findings in relation to causation of IBD is unknown, it has recently been demonstrated in vitro that C. jejuni infection can promote the transport of commensal bacteria across an intact intestinal epithelial monolayer, and so may contribute to persistent inflammation seen in individuals with IBD [28]. In a recent study of a population-based cohort [29], individuals with exposure to Salmonella or Campylobacter gastroenteritis (based on stool culture) and no concurrent diagnosis of IBD were identified.…”
Section: Campylobacter and Nontyphoid Salmonella Speciesmentioning
confidence: 97%
“…34,35 These studies have shown that depletion of membranous cholesterol by cholesterol-sequestering agents (methyl-b-cyclodextrin or filipin) and gene silencing of caveolin-1 abolished endocytosis and transcytosis of nonpathogenic bacteria by epithelial cells in in vitro models after IFNg treatment 15,38 and C. jejuni infection. 45,46 Moreover, caveolin-1 or cholesterol was found colocalized with bacteria-containing endosomes in epithelial cells. 15,45 Invasive pathogens (e.g., Salmonella spp., Shigella spp, and enterohemorrhagic or enteroinvasive Escherichia coli) use their needle-like type III secretion systems to inject effector proteins into epithelial cells, and subsequently manipulate the host cytoskeletal actins for anchorage and entry.…”
Section: Mechanisms Of Intestinal Bacterial Endocytosis By Epithelialmentioning
confidence: 99%
“…[44][45][46] The lumen-dwelling G. lamblia causes diffuse microvilli shortening, TJ disruption and epithelial cell apoptosis, 47,48 that may partly contribute to bacterial penetration. Moreover, it has been reported that intracellular C. jejuni-containing vacuoles deviate from the canonical endosomal pathways, avoiding delivery into lysosomes.…”
Section: Mechanisms Of Intestinal Bacterial Endocytosis By Epithelialmentioning
confidence: 99%